REPRESENTASI MITOS SUKU SASAK DALAM KARYA KOMUNITAS PERUPA ART MANDALIKA PADA PAMERAN “BESIRU” - Nugeraha, Mohammad Ady (Kartala, 2024)
This study examines the representation of Sasak myths in contemporary art from Lombok, focusing on the “Besiru” exhibition organized by the Art Mandalika community in 2023. A qualitative descriptive approach, including observations, direct discussions with artists, and literature reviews, was employed to understand how myths such as Dewi Anjani, Putri Mandalika, and Sekardiu are interpreted in artworks. Using Feldman’s art criticism method—comprising description, formal analysis, interpretation, and evaluation—this research explores the pieces showcased in “Besiru”. The findings indicate that Lombok artists blend traditional elements with modern innovations, creating rich and layered visual narratives. The “Besiru” exhibition serves as a platform to enrich local cultural identity and address relevant social, political, and cultural issues in a modern context. Contemporary art in Lombok functions not only as a medium for individual expression but also as a means to reflect and preserve local wisdom amidst globalization.